2014
DOI: 10.1177/0961203314552832
|View full text |Cite
|
Sign up to set email alerts
|

Application and feasibility of systemic lupus erythematosus reproductive health care quality indicators at a public urban rheumatology clinic

Abstract: Objective Quality indicators (QIs) are evidence-based processes of care designed to represent the current standard of care. Reproductive health QIs for the care of patients with systemic lupus erythematosus (SLE) have recently been developed, and examine areas such as pregnancy screening for autoantibodies, treatment of pregnancy associated antiphospholipid syndrome, and contraceptive counseling. This study was designed to investigate our performance on these QIs and to explore potential gaps in care and demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…The authors found that the rate of avoiding a sexual relationship was higher (50%) and the rates of desire, arousal, lubrication, and orgasm were lower in patients with SLE [ 7 ]. Sexual dysfunction is associated with physical complaints, obsessive-compulsive symptoms, interpersonal sensitivity, psychoticism, decreased vitality, and impaired social function and mental health [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the rate of avoiding a sexual relationship was higher (50%) and the rates of desire, arousal, lubrication, and orgasm were lower in patients with SLE [ 7 ]. Sexual dysfunction is associated with physical complaints, obsessive-compulsive symptoms, interpersonal sensitivity, psychoticism, decreased vitality, and impaired social function and mental health [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Key barriers to performing reproductive health screening and other quality indicators include time and lack of a supportive infrastructure, including efficient ways to document counseling in the EHR. 8,15,16 Authors of several studies have described approaches to teratogenic medication education for adult patients by using computer-based support. [17][18][19] Although satisfaction was high in patients who received counseling, in 1 study of a computerbased support tool, 43% of women still received no medication counseling.…”
Section: Figurementioning
confidence: 99%
“… 5 Studies in patients with SLE reveal that one-third to one-half of patients do not report or do not have documented discussions regarding potential pregnancy risks with initiation of teratogenic medications. 7 8 Lack of adherence to suggested quality measures places our patients at increased risk of harm, but also presents an opportunity for QI.…”
Section: Introductionmentioning
confidence: 99%